Innovative Integration of Islamic Values into the KiVa Program: A Justice and Empathy Framework to Combat Violence in Indonesian Schools - Sita Isna Malyuna; Kusaeri; Evi Fatimatur Rusdiyah; Achmad Maulidi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
School violence, including bullying and sexual violence, poses a significant challenge to the well-being and development of students, particularly in Indonesia. Despite the success of anti-bullying programs like KiVa from Finland in reducing such violence, adapting these programs to the Indonesian context, which is deeply influenced by local cultural and religious values, is crucial for their effectiveness. This study proposes integrating key Islamic values 'adl (justice) and ihsan (empathy) into the KiVa program to create a more inclusive and safe educational environment for Indonesian students. The aim is to address not only the behavior of students but also the underlying societal issues, such as patriarchal norms and social hierarchies, that often fuel sexual violence in schools. Using a Systematic Literature Review (SLR), this research analyzes relevant studies published between 2018 and 2024, focusing on the application of Islamic principles in educational contexts. The findings suggest that integrating 'adl and ihsan enhances KiVa’s effectiveness by fostering fairness, justice, and empathy, which are essential for preventing bullying and sexual violence. The integration of these values ensures a more holistic approach, addressing both the emotional and social aspects of the problem. This research contributes to the body of knowledge by offering a culturally relevant framework that can be adapted to Indonesian schools. Additionally, the study provides policy recommendations to promote teacher training, community engagement, and the inclusion of these values in the school curriculum. Further research is needed to evaluate the long-term effectiveness of this approach in creating safer and more just school environments.